Análise de Perfis Segmentados de Drenagem Para a Avaliação Morfotectônica na Bacia Hidrográfica do Alto Rio Jaguari (SP-MG) - da Silva, Gustavo Pastana Rodrigues; Etchebehere, Mario Lincoln; Saad, Antonio Roberto [UNESP]; Franco-Magalhães, Ana Olívia Barufi (My University, 2012)
This study evaluates the hypothesis that neotectonic processes influence the dynamics of surface processes of the upper Jaguari River hydrographic basin, using the analysis of stream-longitudinal profiles of the most important watercourses and SRTM image photointerpretation. The study region has a predominance of Precambrian crystalline rocks and some discrete occurrences of Cenozoic sediments within a rugged topography. The streams represent a major relief modeling agents, providing the sculpturing of the valleys and the formation of alluvial deposits. Among these parameters, there is the analysis of stream-longitudinal profiles, which can be represented in Cartesian coordinates graphic form (ordered pairs extension of drainage - stream length). The longitudinal profiles tend to show a logarithmic curve conformation, in which reachs out-of-balance may be indicative of recent tectonic activity. We observe that most important local streams, namelly Jaguari, Jacareí and Camanducaia rivers, present two or more significant ruptures in their longitudinal profiles, configuring expressive nick points. This features allow to subdivide each drainage in several reaches, with a specific equation to adjust the ordered pairs, and allowing a better morphometric analysis. The anomalies along the profiles were released on a SRTM image, showing separation of two basic types of morphostructural zones: (1) strongly dissected areas and (2) areas with thick regolith. These zones have sharp and linear contacts, supporting the hypothesis that differential vertical movements are on the way. Thus, the areas of type (1) may represent uplifting morphotectonic blocks and the type (2) zones refer to subsidence blocks, with remarkable influence on the morphogenesis and in the formation/preservation of regolith and younger sedimentary deposits.
Franco-Magalhães - analysis of segmented stream-profile for morphotectonic evaluation of the upper Jaguari River Hydrographic Basin, São Paulo - Minas Gerais State border, Southeastern Brazil
Keywords: Bragantina Region; Geomorphogenesis; Neotectonics; Stream-longitudinal profiles; Upper Jaguarí hydrographic basin